Corrigendum to "Promotional effects of calcination temperature and H2O on the catalytic activity of Al-substituted MnAlO catalysts for low-temperature acetone oxidation" [Chemosphere 301 (2022) 134722]. (May 2023) - Zhang, Wan-Peng; Wu, Kun; Zhao, Junyi; He, Jun; Wang, Leiping; Xiao, Hang; Guo, Jian-Bing; Li, Jian-Rong
Graphical abstract: Image 1